theorem rlrec0 (S: set) (z: nat): $ rlrec z S 0 = z $;
Step | Hyp | Ref | Expression |
---|---|---|---|
2 |
rev 0 = 0 -> lrec z (\\ a1, \\ a2, \ a3, S @ (rev a2, a1, a3)) (rev 0) = lrec z (\\ a1, \\ a2, \ a3, S @ (rev a2, a1, a3)) 0 |
||
3 |
conv rlrec |
rev 0 = 0 -> rlrec z S 0 = lrec z (\\ a1, \\ a2, \ a3, S @ (rev a2, a1, a3)) 0 |
|
4 |
rev 0 = 0 |
||
5 |
rlrec z S 0 = lrec z (\\ a1, \\ a2, \ a3, S @ (rev a2, a1, a3)) 0 |
||
7 |
lrec z (\\ a1, \\ a2, \ a3, S @ (rev a2, a1, a3)) 0 = z |
||
8 |
eqtr* |
rlrec z S 0 = z |